SOCRATIC DIALOGUE AS A RESPONSE TO THE CHALLENGE OF THE EPOCH - Akhmedov B.A. (Sciental Journals Publishing, 2024)
Modern epoch is more and more recognized as a society of risk and the dialogical pedagogy, pedagogy of risk, which is able to agitate mind, to enrage and to excite listeners, consciously provoke them to try different, unusual strategies of life creation, is relevant to it. The formation of new thinking image, where dialogical thinking and dialogical conduct, play important role, can be fundamental respond to the call of epoch.
Keywords: Socratic dialogue; Dialogical thinking; Dialogical conduct; Society of risk; Intercultural dialogue